Aplicação foliar de molibidênio durante a maturação das sementes de soja: efeitos na produtividade, no teor de mo e na qualidade das sementes e nodulação - Milani, Gustavo Lima (2007)
In this work it was evaluated the effect of leaf application of different rates of Mo, in only one application and divided in twice, during the seed maturation, about the yield, content of Mo, seed quality, nodulation and development of the plants. It was realized two assays of crop, in Lavras-MG and Ituiutaba-MG, the others experiments was established in installations of Seed Laboratory of UFLA. It was made leaf applications of Mo, in R5.2 stage to one only application and R5.2 and R5.4 stages to application divided in twice. To two field assays the treatments were: 1 application of 1000g; 1 application of 800g; 1 application of 600g; 1 application of 400g; 2 applications of 500g; 2 applications of 400g; 2 applications of 300g; 2 applications of 200g of Mo per ha and witness. The applications of different rates of Mo, result in one accumulation crescent and linear at quantity of same into seed, independent of one only application or divided. The Mo accumulated of soybean seeds doesn´t affect the yield and the physiological quality of soybean seeds. To evaluation of nodulation and development of plants resultants of enriched seeds was made one assay in greenhouse. The treatments to this assay were: enriched seeds, in two tests, whit 1 application of 1000g; 1 application of 800g; 1 application of 600g; 1 application of 400g; 2 applications of 500g; 2 applications of 400g; 2 applications of 300g; 2 applications of 200g; witness (without Mo) and witness + Mo through of seed treatment. When the plants were in R1 stage these were collected to evaluate: height plant, above and under ground dry mass of plants, nodules and dry mass of nodules per plant and quantity of nitrogen into leaf. The direct treatments of seeds with solution of Mo decrease number nodules per plant. The enrichment of soybean seeds doesn´t damage the nodulation and also doesn´t interfere in the plant development.